Adding social deprivation and family history to cardiovascular risk assessment: the ASSIGN score from the Scottish Heart Health Extended Cohort (SHHEC). Issue 2 (7th November 2006) - Woodward, Mark; Brindle, Peter; Tunstall-Pedoe, Hugh
Abstract : Objective: To improve equity in cardiovascular disease prevention by developing a cardiovascular risk score including social deprivation and family history. Design: The ASSIGN score was derived from cardiovascular outcomes in the Scottish Heart Health Extended Cohort (SHHEC). It was tested against the Framingham cardiovascular risk score in the same database. Setting: Random-sample, risk-factor population surveys across Scotland 1984–87 and North Glasgow 1989, 1992 and 1995. Participants: 6540 men and 6757 women aged 30–74, initially free of cardiovascular disease, ranked for social deprivation by residence postcode using the Scottish Index of Multiple Deprivation (SIMD) and followed for cardiovascular mortality and morbidity through 2005. Results: Classic risk factors, including cigarette dosage, plus deprivation and family history but not obesity, were significant factors in constructing ASSIGN scores for each sex. ASSIGN scores, lower on average, correlated closely with Framingham values for 10-year cardiovascular risk. Discrimination of risk in the SHHEC population was significantly, but marginally, improved overall by ASSIGN. However, the social gradient in cardiovascular event rates was inadequately reflected by the Framingham score, leaving a large social disparity in future victims not identified as high risk. ASSIGN classified more people with social deprivation and positive family history as high risk, anticipated more of their events, and abolished this gradient. Conclusion: Conventional cardiovascular scores fail to target social gradients in disease. By including unattributed risk from deprivation, ASSIGN shifts preventive treatment towards the socially deprived. Family history is valuable not least as an approach to ethnic susceptibility. ASSIGN merits further evaluation for clinical use.